Prognosis of cerebral lipiodol embolism caused by transarterial chemoembolization. (2nd October 2016) - Pai, Yen-Wei; Hsieh, Peiyuan F.; Tung, Hsin; Wu, Chun-Ying; Ching, Congo T. S.; Chang, Ming-Hong
Abstract : Objectives: Transarterial chemoembolization (TACE) plays an essential role in the management of unresectable hepatocellular cell carcinoma and other hepatic neoplasms. Cerebral lipiodol embolism (CLE) is a rare complication of TACE and its prognostic factors have not been well studied. The aim of this paper was to elucidate the prognostic factors of CLE based on clinical data obtained from our patients and cases published since 2004. Methods: We present two patients with CLE, analyze the clinical data, and review all CLE cases published since 2004. A poor outcome was defined as stupor, coma, quadriplegia, or death within 45 days. Patients who had other neurological conditions within 45 days were considered as having a good outcome. Results: The rate of poor outcome was 25.7% (9/35). Compared with the patients with good outcome, those with poor outcome were older (mean age 68.3 ± 7.3 vs. 58.3 ± 10.6 years, p  = 0.03), more often female (76.9% vs. male 33.3%, p  = 0.02), and more likely chemoembolized via both the right hepatic and right inferior phrenic arteries (44.4 vs. 8.7%, p  = 0.02). Discussion: The prognosis of CLE was related to age, gender, and the arteries selected for injection.